Akumulasi Biomassa Tumbuhan Poaceae di Bawah Cekaman Karbon Monoksida (CO) - Puspitasari, Laksmi; Wahyuni, Resti; Pasaribu, Pinta Omas; Saputri, Rinny (Journal of Natural Sciences, 2025)
Air pollution caused by motor vehicle emissions is a significant environmental issue in Indonesia. One of the main pollutants from these emissions is carbon monoxide (CO), which can harm the environment and inhibit plant growth. High carbon monoxide exposure can cause plants to experience stress. This study aims to analyze the biomass accumulation of several plant species from the Poaceae family (Setaria plicata, Rottboellia cochinchinensis, Eleusine indica, and Paspalum conjugatum) under carbon monoxide exposure. The research method used was an experimental study with a Two-Factor Completely Randomized Design (CRD). The factors tested included plant species (four types) and the frequency of carbon monoxide exposure (three levels), with each treatment repeated three times. The results showed that the shoot dry weight was influenced by the plant species and the frequency of carbon monoxide exposure separately, with no interaction between the two factors. Rottboellia cochinchinensis had the highest shoot and root dry weight accumulation compared to the other species, while Paspalum conjugatum had the lowest biomass accumulation. The frequency of carbon monoxide exposure twice a week for two consecutive weeks resulted in the lowest shoot dry weight among the Poaceae plants.